Discursive Transformations in Vietnamese Children’s Literature (1975–2024): From Revolutionary Ideals to Postmodern Sensibilities (KEMANUSIAAN The Asian Journal of Humanities, 2026)
This article examines discursive transformations in Vietnamese children’s literature from 1975 to 2024 and traces the shift from collective, revolutionary ideals to more individualised and postmodern modes of representation. Situated in a post-war context reshaped by the Doi Moi reforms and subsequent globalisation, Vietnamese children’s literature has operated as a cultural institution for the construction of collective memory, images of childhood and social subjectivity. Drawing on theories of children’s literature and post-war memory studies, this study analyses 30 representative texts through literary discourse analysis, content analysis and intertextual analysis. The findings show how evolving modes of expression both reflect and help shape Vietnam’s broader sociocultural transformations. By offering a case study grounded in Vietnam’s distinctive socialist and reform-oriented context, the article broadens global scholarship on post-war children’s literature and makes theoretical as well as practical contributions to research on discourse, cultural memory and post-war childhoods.